Performance Measurement Analysis Of PT NPS Using The Balance Scorecard Method: Analisis Pengukuran Kinerja PT NPS Menggunakan Metode Balance Scorecard - Fatharisa Ingke Maulida; Rr. Rochmoeljati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
PT NPS is a company in the field of power plant maintenance services, then developed into a company engaged in power plant operation and maintenance services. Along with this development, PT NPS's competitiveness continues to be strengthened both in terms of finance, operations and human resources by forming a strong corporate culture. Therefore, it is important for PT NPS to measure performance in order to improve performance and compete with similar companies. One way to assess performance is to use the Balance Scorecard, which focuses on strategy and includes financial, internal process, operational, and learning and development perspectives. The data used in this observational study are in the form of company financial reports and employee data from 2020-2022. The findings from this observational study indicate that the financial perspective is considered less than good, but is balanced by the net profit value which is considered very good. The operational and internal business perspective is considered good but the learning and growth perspective is considered less than good. Employee productivity is considered very good because it shows a significant increase every year. This study can be used by PT PNS to continuously develop more optimal strategies so that they can experience improvements which will later also have an impact on the company's performance.